One-way Teaching - Understanding Power Establishing Strategy and Teaching Strategy in "Everyday Grammar TV" - Maulana, Rivki Surya; Hidayat, Didin Nuruddin; Husna, Nida (English Education: Jurnal Tadris Bahasa Inggris, 2025)
Youtube has been rigorously studied in the realm of ESL and EFL. Nonetheless, these studies focused on the usage of Youtube as a teaching aid. The present study employs a qualitative research design to analyze the teaching methods and power establishment in VOA Learning English's "Everyday Grammar TV" series. This study examines how Youtube can be used as a learning source by itself. Using Critical Discourse Analysis (CDA) as outlined by Fairclough, the research examines the language text, discourse practices, and discursive events within the series. The findings indicate that the teaching method used is Content-Based Instruction (CBI), which integrates language learning with educational content. Additionally, power is established through the use of individualization, specifically by addressing one of the hosts with academic titles, thereby emphasizing their authority and expertise. This study provides insights into the dynamics of educational media and the role of language in establishing power. Further studies could focus to investigate how viewers perceive and internalize these power structures. Understanding how learners interpret and respond to the use of individualization and other power strategies would provide deeper insights into the effectiveness of these techniques in fostering respect and engagement.